NANOPARTICLE REINFORCED LIGHTWEIGHT METAL COMPOSITES - Li, Qianqian; Markcoons, Daniel; Xu, Zhuocheng; Hisham, Syazana; Nasiri, Samaneh; Shaffer, Milo S.P.; Zaiser, Michael (ECCM 2022 - Proceedings of the 20th European Conference on Composite Materials: Composites Meet Sustainability, 2022)
The interest to use carbon nanotubes (CNTs) to reinforce light metals has increased in recent years due to their potential application as lightweight high performance materials. One challenge in producing CNT composites is to achieve a homogenous dispersion of CNTs in the metal matrix. In order to effectively disperse CNTs in the Mg melt, we for the first time introduced the idea of using metal coated CNTs to promote the integration into Mg matrix. In this paper, Pt was selected to coat the CNT surface. TEM and EDX confirm that atomic Pt has been successfully deposited onto CNTs. The dispersion and stability of metal coated CNTs in solution have been investigated and compared to CNTs without metal coating. The Pt coated CNT reinforced Mg composites were also produced via a melt stirring process. The mechanical properties of such composites also showed a clear upward tendency, which we attribute to the Pt coating to help the dispersion of CNTs.
CRIS-Team Scopus Importer:2024-12-16
Keywords: dispersion; Lightweight metal composites; carbon nanotubes; wettability